Tromsø’s urban toll, sustainable urban planning put to the test of the Arctic peripherality - Tortosa, Grégoire (Cybergeo, 2023)
International audience This article examines the process of setting up the Tromsø city toll, whose very late implementation (2021) raises questions in a country that has made environmental exemplarity a lever for global integration. The article offers a geo-historic reading of this process from a center/periphery prism, discussing the reluctancy of local residents to sustainable land-use planning and their singular bond to car transport. At a time when, elsewhere in Europe, the reconfiguring of centre/periphery relationships is marked by the empowerment of local states in the face of central state supervision, the establishment of the Tromsø city toll is distinctive in that it maintains a strong duality between the southern centrality and its northern periphery. The establishment of the city toll symbolizes the end of the municipality’s State-granted special regime, and reflects Tromsø’s changing status, from the country’s Northern periphery to the arctic projection of Oslo. Se aborda el proceso de implementación del peaje urbano en Tromsø, cuya tardía puesta en marcha (2021) plantea interrogantes en un país que ha hecho de la ejemplaridad medioambiental una marca de integración global. El artículo propone una lectura geo histórica del proceso de adopción del peaje a través del prisma de las relaciones centro-periferia, explorando las raíces de las reticencias locales a los principios nacionales de planificación urbana sostenible y buscando comprender el singular apego de los habitantes al automóvil. En un contexto donde el resto de Europa la reconfiguración de las relaciones centro/periferia está marcada por el empoderamiento de las ciudades o gobiernos locales frente a una tutela del Estado central, el establecimiento del peaje urbano de Tromsø destaca por mantener una fuerte dualidad entre la centralidad meridional y su periferia septentrional. Además, su puesta en marcha marca el final de un régimen especial otorgado al Municipio por parte del Estado, y revela el cambio de estatus y rol de la ciudad, que ...